SHIFTBIO'S ESM TECHNOLOGY: UNLOCKING NEW POSSIBILITIES IN DRUG TARGETING AND DELIVERY WITH EV ENGINEERING - Kim, Y.; Nam, G.; Kim, I. (CYTOTHERAPY, 2024)
Background & Aim SHIFTBIO aims to provide effective solutions for acute organ failure by developing innovative treatments through Cell-Free Nanotherapy Platform Technologies, transforming traditional therapeutic approaches and promising to redefine patient outcomes. At the heart of this innovation are engineered Extracellular Vesicles (EVs), derived from stem cells, which are designed to optimize drug delivery and efficacy for various diseases, overcoming the limitations of current drug modalities. Methods, Results & Conclusion: Methods SHIFTBIO developed the Extracellular vesicle Sorting Motif (ESM), a specific amino acid sequence that enhances the sorting of specific payloads into EVs. This allows for the precise targeting and delivery of drugs to pathological cells. SHIFTBIO's ESM platform stands out from existing EV engineering methods by its ability to engineer a broad range of cells and to load multiple types of cargo, enabling complex therapeutic strategies. Results SHIFTBIO has developed two main pipelines utilizing ESM technology: 1. SBI-102 (SIRP-EV): This pipeline utilizes SIRPα protein expressed on stem cell-derived EVs to enhance ability of the immune system for targeting pathological cells. It shows great promise in treating severe liver injuries, including alcoholic hepatitis and acute liver failure. SIRP-EV is advantageous over CD47 antibody treatments due to its preferential accumulation in inflamed tissues and reduced toxicity. 2. SBI-201 (HIF1α-EV): This involves loading HIF1α into EVs, targeting monocytes and macrophages. It has shown significant potential in treating inflammatory diseases, evidenced by improved survival rates in sepsis models. HIF1α-EV induces the differentiation of monocytes into resolutive macrophages. Conclusion SHIFTBIO's Cell-Free Nanotherapy Platform Technologies, leveraging the ESM platform, represent a significant breakthrough in regenerative immunotherapies. Guided by the mission of "Giving Second Chance to Life, Cure the Incurables", SHIFTBIO aims to revolutionize treatment options for patients with rare and untreatable diseases, positioning to lead a new era of next-generation cell-free therapies.